Outbreaks of methicillin-resistant Staphylococcus aureus among staff and dogs in Swedish small animal hospitals. (April 2014) - Grönlund Andersson, Ulrika; Wallensten, Anders; Hæggman, Sara; Greko, Christina; Hedin, Göran; Hökeberg, Ingegerd; Lindström, Fredrik; Olsson-Liljequist, Barbro; Smedjegård, Jan; Söderblom, Tomas; Windahl, Ulrika; Struwe, Johan
Abstract Methicillin-resistant Staphylococcus aureus (MRSA) was found in a dog for the first time in Sweden in 2006. Between October 2006 and May 2007, MRSA was diagnosed in 7 more dogs that had been treated in 3 different small animal hospitals, located 150–200 km apart, in different counties of Sweden. Screening of the animal hospital staff and environment in these small animal hospitals showed 20 of 152 staff to be positive for MRSA, with rates between 2% and 18% in the different hospitals, while all 128 environmental samples were negative. All MRSA isolates from dogs and staff belonged to spa type t032, were Panton–Valentine leukocidin (PVL)-negative, and had indistinguishable pulsed-field gel electrophoresis patterns, except for 2 isolates with closely related patterns. To our knowledge, this is the first report of multiple outbreaks of MRSA in dogs caused by the same strain within a short time frame, and appearing in a country with low prevalence of MRSA in both humans and dogs. This highlights the importance of infection control programs in animal hospitals and in animal health care. Awareness of MRSA as an occupational risk for veterinary personnel is essential.